Pengendalian Kualitas Produk Coil Vapor Pada CV. ABC Dengan Menggunakan Statiscal Process Control - Vincent Oktavianus Pranata; Erni Puspanantasari Putri (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
ABC is a business entity that focuses on producing electric cigarette coils. As one of the steps to satisfy consumers, one aspect that is always considered in every production process is the quality of electric cigarette coil products so that consumer satisfaction is maintained. In the production process, defective products are found every day. The purpose of this research is to see whether the existing production process is still within safe control limits and to analyze the causes of problems if the data exceeds the existing controls. The research method used is using production data and product defects data using Statistical Process Control data processing using Microsoft Excel software which is then processed to analyze the causes of problems and provide advice to CV. The results of the quality control process from 53 observations found 6 observations that exceeded the lower and upper limits, so an analysis was needed. From the existing analysis it was found that the problems that occurred were caused by fatigued workers, errors in methods, and maintenance of equipment that was rarely done.